1978
DOI: 10.1002/ajh.2830050303
|View full text |Cite
|
Sign up to set email alerts
|

Elevated plasma levels of fibrinopeptide a during sickle cell anemia pain crisis–evidence for intravascular coagulation

Abstract: A role for coagulation in the pathogenesis of sickle cell anemia (SCA) pain crisis has long been suspected. We have observed evidence for in vivo coagulation in patients with SCA during pain crisis utilizing a radioimmunoassay for fibrinopeptide A (FPA). Since the proteolytic activity of thrombin results in the release of FPA from fibrinogen, plasma levels of FPA may be used as an index of in vivo thrombin activity. In 20 normal controls FPA plasma levels had a range of 0.6-1.4 ng/ml and a mean of 0.7 * 0.2 ng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

1986
1986
2004
2004

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…Such spicules, which have been found in the plasma of patients with sickle cell disease [20,21], dramatically increase the rate of thrombin formation [ 191. Several investigators have reported indirect evidence of intravascular thrombin formation in subjects with sickle cell disease, generally in the form of elevated levels of fibrinopeptide A [22], signs of platelet activation [23], and consumption of protein C [24].…”
Section: Discussionmentioning
confidence: 99%
“…Such spicules, which have been found in the plasma of patients with sickle cell disease [20,21], dramatically increase the rate of thrombin formation [ 191. Several investigators have reported indirect evidence of intravascular thrombin formation in subjects with sickle cell disease, generally in the form of elevated levels of fibrinopeptide A [22], signs of platelet activation [23], and consumption of protein C [24].…”
Section: Discussionmentioning
confidence: 99%
“…those observed by Whitaker et al [7] in sub jects with established macrovascular throm bosis (deep-vein thrombosis, pulmonary em bolism, and arterial thromboembolism) [7], The levels observed in most steady-state pa tients are lower, suggesting that activation of coagulation in the steady state is less pro nounced. The normal fpa levels previously reported in the steady state [6] may reflect a lower sensitivity of plasma fpa levels to lowgrade activation of coagulation, perhaps due to the very short half-life (approximately 3 min) of this peptide fragment in vivo [5]. Studies comparing the levels of fpa and D-dimer in steady-state sickle cell subjects are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Fibrinopeptide A (fpa) is pro duced by the action of thrombin on the alpha chain of fibrinogen, and is the first fragment produced in the transformation of fibrino gen to fibrin [5], fpa has been reported to be elevated during painful crisis, but to be nor mal in uncomplicated sickle cell disease dur ing the steady state [6]. fpa levels in plasma are very sensitive to artifact due to in vitro thrombin activity, so that flawless venipunc ture technique, special anticoagulants, and prompt processing of plasma to remove cross-reacting fibrinogen are necessary to ob tain valid results.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple physiologic events are thought to contribute to vaso-occlusion, including hemoglobin S polymerization with consequent RBC deformation [1], cell dehydration leading to increased hemoglobin polymerization [2,3], RBC adhesion to endothelial cells and extracellular matrix (ECM) proteins [4], and activation of coagulation [5][6][7]. Red blood cells containing predominantly hemoglobin S (SS RBC) adhere most avidly to laminin among ECM proteins [8].…”
Section: Introductionmentioning
confidence: 99%